10 years of 25-hydroxyvitamin-D testing by LC-MS/MS-trends in vitamin-D deficiency and sufficiency - Galior, Kornelia (Bone Rep, 2018)
In early 2000's vitamin-D deficiency was shown to be prevalent in several countries including the United States (US). Studies exploring the role of vitamin-D metabolism in diverse disease pathways generated an increased demand for vitamin-D supplementation and an immense public interest in measurement of vitamin-D metabolite levels. In this report, we review the role of vitamin-D metabolism in disease processes, clinical utility of measuring vitamin-D metabolites including 25-hydroxyvitamin-D (25(OH)D), 1,25-dihydroxyvitamin-D and 24,25-dihydroxyvitamin-D and discuss vitamin-D assay methodologies including immunoassays and liquid chromatography mass spectrometry (LC-MS/MS) assays. We also provide examples of vitamin-D toxicity and insight into the trends in serum 25(OH)D levels in the US population based on 10 years of data from on serum 25(OH)D values from ~5,000,000 patients who were tested at the Mayo Medical Laboratories between February 2007–February 2017.